Water and food security: stumbling toward Malthusian oblivion or pioneering cornucopia? - Chartres, Colin J. (2012)
The International Water Management Institute (IWMI) was established in Sri Lanka by the Ford Foundation and others in the mid-1980s. Today, IWMI works in about 20 countries. Colin Chartres reflected on the history of IWMI's work and described important studies that have advanced the understanding of water and food.